(untitled) (Eurasian Research Bulletin, 2023)
One of the ways to attract the attention of schoolchildren is non-standard forms of teaching – they «attract the attention of students, increase their interest in science and contribute to better learning of the material.» Non-standard forms of the lesson include excursion lessons, thematic lessons, didactic games and, of course, work in groups. Active methods of language teaching, which are becoming increasingly popular, play an important role here. Active teaching methods are methods that «encourage students to actively think and practice in the process of mastering educational material.» N.M. Kleimenova notes that «the knowledge obtained empirically is the most profound and profound